Potentiality of Acacia riparia as a forage species in the northeast of Cesar State, Colombia (Bioagro, 2020)
In the northeast region of the Cesar State in Colombia there are fodder legumes which are adapted to dry climates and whose ecological and nutritional characteristics are unknown, as the case of the Acacia riparia. The main objective of this study was to evaluate the potential of this species as forage plant in the specific zone of the Cesar State. A botanical inventory was done using a sampling unit of 0.1 ha to determine the richness of the woody plants with a girth at breast height of at least 7 cm. Nutritional characteristics of A. riparia leaves were determined by bromatological analysis and in vitro digestibility. The research showed the presence of different fodder legumes where A. riparia was one of the three more representative species of this region, with a relatively high importance value index (IVI=0,192) only under Prosopis juliflora (IVI=0.750) y Samanea saman (IVI=0.655). The species contains 22.6 % protein and 50.8 % digestibility in vitro. The ecological importance and nutritional characteristics of this species as potential forage for ruminants was demonstrated.
Keywords: Acacia; ecological importance; forage; in vitro digestibility; ruminants